Cultural diversities in education in the North - Johansson, Gunilla (Luleå tekniska universitet, Pedagogik, språk och Ämnesdidaktik, 2007)
The purpose of this study is to highlight some perspectives of Teacher Education in the North, especially connected to cultural diversities and the richness of the Sámi Schools in Sweden. Minorities and immigrants are almost invisible in the documents. Indigenous based education can evaluate experiences from the attempts to define and implement education in terms of a curriculum interpreted on the base of the national curriculum. The lack of experience in the educational decision making due to the Sámi culture and the discontinuity between school culture and community culture is obvious. Cultural diversities as well as dilemmas with language are often seen as obstacles. Development of culturally appropriate curriculum for cultural diversities, in this case Sámi schools is pointed out as an important area for research and development. The second area for development is teacher's professional identity in connection with cultural understanding and cultural diversities. A third area is knowledge of parental involvement in cultural diversities in school development. Cooperation with parents, elders, extended family and the indigenous community is an area of interest for future research. Teacher education is questioned in terms of democracy and tendencies of a mainstreamed education of teachers. A more receptive education based on the indigenous peoples needs is discussed. International research is highlighting cultural understanding, colonizing and decolonizing processes. A teacher working in a Sámi school needs a practice based and theoretical grounded teacher education. There is a lack of in service training of teachers in the same areas. Networks between the Teacher Educations Institutions in the North, in Sweden, Finland and Norway in Sápmi could serve as a point of departure in developing a research based education for teachers working with cultural diversities in the North. Godkänd; 2007; 20070412 (biem)